1991
DOI: 10.1159/000114365
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Mauthner Cell in Sensorimotor Integration by the Brain Stem Escape Network

Abstract: The Mauthner neurons have become synonymous with the C start evasive response of fishes. C starts are a two-part movement pattern. First, the fish bends its body so that it has a C-like profile (stage 1) when viewed from above. Second, the fish rapidly accelerates away from its starting position (stage 2). Until recently, it has not been possible to determine the contribution of Mauthner cell activity to the expression of this behavior. In this paper we focus on three of our recent papers that address this iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
94
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(99 citation statements)
references
References 16 publications
4
94
0
1
Order By: Relevance
“…In zebrafish, fast responses initiated with a C-bend (C-start responses) require just three bilateral pairs of reticulospinal neurons including the Mauthner cells (Liu and Fetcho, 1999). These cells receive multimodal sensory input (Zottoli et al, 1995) and have been previously suggested as a model for sensorimotor integration in the brainstem without the complication of corticospinal influences found in mammals (Eaton et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish, fast responses initiated with a C-bend (C-start responses) require just three bilateral pairs of reticulospinal neurons including the Mauthner cells (Liu and Fetcho, 1999). These cells receive multimodal sensory input (Zottoli et al, 1995) and have been previously suggested as a model for sensorimotor integration in the brainstem without the complication of corticospinal influences found in mammals (Eaton et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Few attempts have been made to link identifiable premotor systems to certain behaviors. Best known are the Mauthner neuron (or M cell) and its segmental homologs MiD2 and MiD3, which play a critical role in fast-start escapes (Zottoli et al, 1987;Faber et al, 1989;Eaton et al, 1991;Svoboda and Fetcho, 1996;O'Malley et al, 1996;Liu and Fetcho, 1999;Eaton et al, 2001;Zottoli et al, 1987). However, even the apparently simple startle circuit is complex: stimuli eliciting escapes activate many other RS neurons in addition to these three pairs (Gahtan et al, 2002), and even triple ablations do not eliminate startle responses altogether (Liu and Fetcho, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although some escape responses occur in this amount of time, i.e. crayfish tailflip <20路ms (Krasne and Wine, 1984) and fish Mauthner-mediated C-start 14路ms (Eaton et al, 1991), many responses have latencies of 40路ms or more, i.e. cricket terrestrial response 87路ms (Tauber and Camhi, 1995), locust jump up to 1100路ms (Heitler, 1974), insect flight responses 40-240路ms, depending on insect and response type (Nolen and Hoy, 1986;.…”
Section: Introductionmentioning
confidence: 99%